Osteoblast‐derived factors promote metastatic potential in human prostate cancer cells, in part via non‐canonical transforming growth factor β (TGFβ) signaling. Issue 6 (31st January 2018) - Karlsson, Terese; Sundar, Reshma; Widmark, Anders; Landström, Maréne; Persson, Emma
Abstract : Background: Transforming growth factor β (TGFβ) functions as a double‐edged sword in prostate cancer tumorigenesis. In initial stages of the disease, TGFβ acts as a growth inhibitor upon tumor cells, whereas it in later stages of disease rather promotes invasion and metastatic potential. One well‐known cellular source of TGFβ in the bone metastatic site is the bone‐forming osteoblasts. Here we have studied the effects by osteoblast‐derived factors on metastatic potential in several human prostate cancer cell lines. Methods: Effects on metastatic potential in prostate cancer cells by osteoblast‐derived factors were studied in vitro using several methods, including Transwell migration and evaluation of formation of pro‐migratory protrusions. Confocal microscopy was used to evaluate possible changes in differentiation state in tumor cells by analysis of markers for epithelial‐to‐mesenchymal transition (EMT). The Matrigel‐on‐top 3D culture method was used for further assessment of metastatic characteristics in tumor cells by analysis of formation of filopodium‐like protrusions (FLPs). Results: Osteoblast‐derived factors increased migration of PC‐3U cells, an effect less prominent in cells overexpressing a mutated type I TGFβ receptor (TβRI) preventing non‐canonical TRAF6‐dependent TGFβ signaling. Osteoblast‐derived factors also increased the formation of long protrusions and loss of cell‐cell contacts in PC‐3U cells, suggesting induction of a more aggressive phenotype. In addition, treatment with TGFβ or osteoblast‐derived factors of PC‐3U cells in Matrigel‐on‐top 3D cultures promoted formation of FLPs, previously shown to be essential for metastatic establishment. Conclusions: These findings suggests that factors secreted from osteoblasts, including TGFβ, can induce several cellular traits involved in metastatic potential of PC‐3U cells, further strengthening the role for bone cells to promote metastatic tumor cell behavior.